2020
DOI: 10.1002/ep.13396
|View full text |Cite
|
Sign up to set email alerts
|

Thermo‐economic feasibility of a hybrid wind turbine/PV/gas generator energy system for application in a residential complex in Tehran, Iran

Abstract: The randomness of generated power by renewable energy resources has led experts in this field to provide sustained and permanent load supply with hybrid renewable energy systems (HRESs). This study investigates the modeling of an off‐grid HRES based on the wind turbine/photovoltaic/gas generator for supplying the consumption of a residential complex in Tehran (capital of Iran). To this end, the HOMER software has been implemented. After calculations, the capital cost and cost of energy of each component are es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The total capital expenditure during the lifetime (20 years) was calculated and compared with the grid electricity costs, a conventional method in Iran, to evaluate the proposed Qolipour et al [11] 2016 Iran Ardabil province Household * * * HAWT Off-grid Mohammadi et al [12] 2018 Iran Hesarek Household * * * HAWT Off-grid Akbari et al [13] 2018 Iran Khvaf -* * HAWT On-grid Ashrafi Gudarzi et al [14] 2019 Iran Tehran Residential complex * * * HAWT Off-grid Abbaszadeh et al [15] 2020 Iran Tehran Residential complex * * * HAWT Off-grid Farahi and Fazelpour [16] 2018 Iran Tehran, Kish, and Binaloud…”
Section: Economic Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The total capital expenditure during the lifetime (20 years) was calculated and compared with the grid electricity costs, a conventional method in Iran, to evaluate the proposed Qolipour et al [11] 2016 Iran Ardabil province Household * * * HAWT Off-grid Mohammadi et al [12] 2018 Iran Hesarek Household * * * HAWT Off-grid Akbari et al [13] 2018 Iran Khvaf -* * HAWT On-grid Ashrafi Gudarzi et al [14] 2019 Iran Tehran Residential complex * * * HAWT Off-grid Abbaszadeh et al [15] 2020 Iran Tehran Residential complex * * * HAWT Off-grid Farahi and Fazelpour [16] 2018 Iran Tehran, Kish, and Binaloud…”
Section: Economic Analysismentioning
confidence: 99%
“…They concluded that the optimal design providing 93% of the electricity includes 13-kW PV, 10-kW inverter, and four horizontal axis wind turbines (HAWT) of 100 kW in ongrid mode with an initial investment of 440 000 $ has a 4-year payback period. For a residential complex in Tehran, Ashrafi Gudarzi et al [14] studied a WT-PV-battery hybrid system; additionally, Abbaszadeh et al [15] researched a WT-PV-gas generator system. Each separately indicated that hybrid systems instead of diesel systems could significantly reduce GHG emissions while achieving cost savings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7] In terms of optimal planning of energy management system (EMS), many studies have been carried out in order to minimize cost of energy and achieve reliable electricity service. [8][9][10][11][12][13] For example, Yusheng et al 14 introduced a general method to determine the optimal economic dispatch for the grid-connected MG including cascade hydropower/photovoltaic (PV)/wind turbine taking into account cascade reservoir connection. At the beginning, the authors studied the complementing work of PV/wind turbine and proposed the method of capacity calculation in addition to minimization of cumulative fluctuations.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, onshore wind turbines affect real estate prices in nearby single-family houses and holiday resorts, reducing their value [43]. In order to fully exploit the possibilities of supplying housing estates, in addition to wind energy, photovoltaics and power supply from an external generator are also used to ensure a constant energy supply [44][45][46][47][48][49][50]. The use of natural energy sources (wind and sun) alone can be unreliable due to their unstable nature.…”
Section: Introductionmentioning
confidence: 99%